Determinants of Under-five Mortality Due to Pneumonia: A Negative Binomial Regression Analysis - Dhea Prawidia; Fitri Kartiasih; Lidya Zhafirah; Nurzikri Saputra; Uma Sahu (Universitas Bumigora, 2023)
Pneumonia is one of the main causes of under-five mortality in Indonesia. In under-fives, pneumonia is the number one killer in the world. Meanwhile, in Indonesia, it ranks second after diarrhea. On average, the disease affects half a million children a year. This study aims to identify and analyze the risk of variables that affect the number of under-five mortality due to pneumonia in Indonesia in 2021. The novelty of this research focuses on the macro variables used, making it easier for policy makers to make decisions. The research method used is negative binomial regression. The results showed that the highest number of under-five mortality due to pneumonia was in Central Java Province. Meanwhile, the lowest was in Jambi Province, South Sumatra, Riau Islands, DKI Jakarta, North Kalimantan, Southeast Sulawesi, and Papua. The per capita income significantly reduces the number of under-five mortality due to pneumonia, while the number of under-fives with severe pneumonia significantly reduces the number of under-five mortality due to pneumonia in Indonesia. The government needs attention to reduce the death rate of children under five due to pneumonia by providing social protection in the fields of health and education for underprivileged communities.